2021
DOI: 10.1177/2473011420981926
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use Among Foot and Ankle Orthopedic Surgeons

Abstract: Background: Digital media is an effective tool to enhance brand recognition and is currently referenced by more than 40% of orthopedic patients when selecting a physician. The purpose of this study was to evaluate the use of social media among foot and ankle (F&A) orthopedic surgeons, and the impact of that social media presence on scores of a physician-rated website (PRW). Methods: Randomly selected F&A orthopedic surgeons from all major geographical locations across the United States were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
5
17
1
3
Order By: Relevance
“…(1) According to Bakhsh W (2014) discussed in Garofolo's (2021) research, online social platforms have reshaped communication in healthcare and contributed to the shift toward patient satisfactionbased models. (5) Using Facebook in hospitals is very important in Italy as a communication tool. Research conducted with 1352 hospitals found that almost half of the hospitals have a Facebook page and use social media every week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) According to Bakhsh W (2014) discussed in Garofolo's (2021) research, online social platforms have reshaped communication in healthcare and contributed to the shift toward patient satisfactionbased models. (5) Using Facebook in hospitals is very important in Italy as a communication tool. Research conducted with 1352 hospitals found that almost half of the hospitals have a Facebook page and use social media every week.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that 80% of patients use the internet for health-related questions. (5) Another study in 2013 found that the first motive for patients to use health-related social media is to seek information about health, disease, or treatment of disease; Twitter is the most used platform for this information. (3) In recent years, health services have been delivered remotely through telemedicine applications, the best access to care for some people, such as those who are isolated or in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring that patients have appropriate expectations and are properly educated about the risks of surgery may represent the best way to improve patient trust while simultaneously boosting review scores. [33][34][35][36][37] This study is not without limitations. Our study only included reviews listed on Yelp.com, Healthgrades.com, and Vitals.com.…”
Section: Figurementioning
confidence: 95%
“…In internationalen Studien konnte gezeigt werden, dass bis zu 88% der Ärzte und des Pflegepersonals regelmäßig soziale Medien nutzen 9 . Die Häufigkeit der dienstlichen Nutzung von sozialen Netzwerken durch Orthopäden und Unfallchirurgen wurde in Studien mit 37,0 – 65,7% beschrieben 10 , 11 , 12 , 13 , 14 , 15 , 16 . Die am häufigsten beruflich eingesetzten Plattformen sind LinkedIn und Facebook 10 , 11 , 12 , 13 , 15 , 17 , 18 , während Instagram eher von jüngeren Kollegen verwendet wird 10 .…”
unclassified
“…Die Häufigkeit der dienstlichen Nutzung von sozialen Netzwerken durch Orthopäden und Unfallchirurgen wurde in Studien mit 37,0 – 65,7% beschrieben 10 , 11 , 12 , 13 , 14 , 15 , 16 . Die am häufigsten beruflich eingesetzten Plattformen sind LinkedIn und Facebook 10 , 11 , 12 , 13 , 15 , 17 , 18 , während Instagram eher von jüngeren Kollegen verwendet wird 10 . Petersen et al geben in ihrem Übersichtsartikel „Social Media in Orthopädie und Unfallchirurgie“ einen guten Überblick über die existierenden Plattformen und deren Anwendungsmöglichkeiten 19 .…”
unclassified